Pengukuran Kinerja Portofolio Optimal Model Stochastic Dominance Pada Indeks LQ-45 Masa Pandemi Covid-19 - Sintia Arzelina; Media Rosha (UNIVERSITAS NEGERI PADANG, 2021)
Abstract－ Investment is one aspect that is in the spotlight of investors during the outbreak of the Covid-19 pandemic. Investing cannot be separated from the words return and risk, to optimize the rate of return and minimize risk, a portfolio of Stochastic Dominance models can be formed. This study aims to form an optimal portfolio of the LQ-45 Index during the Covid-19 pandemic by applying the stochastic dominance model as well as measuring the optimal portfolio performance formed by three measurement methods, namely the Jensen Index, Treynor Index, and the Jensen Index. Based on the analysis conducted on 10 stocks, the LQ-45 Index produces 9 dominant stocks. The nine stocks and their proportions are INCO 17.587%, ERAA 14.286%, INKP 14.286%, SCMA 14.285%, TBIG 14.286%, ANTM 14.286%, PTPP 3.571%, TKIM 3.571%, and WIKA 3.571%. The expected return and risk generated by the portfolio formed are 0.1267134 and 0.00762, respectively. Performance measurement with the Sharpe Index, Treynor Index, and Jensen Index both produce positive performance, in other words the formed portfolio has a good performance.